O-016 Treatment of Intracranial Aneurysms with the LUNA AES Updated. (14th July 2013) - Piotin, M; Biondi, A; Sourour, N; Mounayer, C; Andersson, T; Söderman, M; Mangiafico, S; Jaworski, M; Anxionnat, R; Blanc, R
Abstract : Purpose: The LUNA Aneurysm Embolisation System (AES) is a new self-expanding ovoid device that serves as an intra saccular flow diverter as well as a scaffold for endothelisation across the neck. The objective of this prospective clinical study aiming to include a total of 63 patients was to evaluate the ability of the AES to occlude intracranial aneurysms while maintaining patency of the parent artery. Materials and Methods: Immediate post-implantation occlusion grade (complete obliteration of the aneurysm including the neck), near-complete (persistence of any portion of the original defect of the arterial wall), or incomplete (any opacification of the sac) compared to baseline), and parent vessel compromise were evaluated. Patients underwent neurological testing with the Modified Rankin Scale and the National Institute of Health Stroke Scale (NIHSS) at baseline and time of discharge. Follow-up included clinical assessment at one, 3, 6, 9 and 12 months, and angiographic follow-up at 6 and 12 months. Results: 50 patients (9 men) with 47 unruptured and 4 ruptured saccular aneurysms (38 bifurcation, 13 sidewall, sizes from 3.9 to 10.1 mm) were enrolled to date in the study. In all but 2 aneurysms (2 failed procedure converted in coiling) 1 LUNA AES was deployed per aneurysm. In 5 cases, the LUNA AES placement was carried out with balloon microcatheter assistance. In one case, the LUNA AES placement was carried out with a stent. In 1 case, AES placement led to aneurysm perforation that was controlled by temporary balloon occlusion and heparin reversion. In 1 case, thrombo-embolic complication was treated with i.a. injection of Abciximab. Clinical follow up was uneventful in all but 2 patients (one sustained SAH from a contralateral MCA aneurysm, one had GI bleeding). Immediate complete/near complete occlusion was obtained in 22.5% (22/49). At 6 month follow-up, complete/near complete occlusion was obtained in 70.4% (19/27). There was no parent artery stenosis or occlusion. None of the treated aneurysm (re)bled during follow-up. Conclusion: Preliminary results demonstrate good safety profile. Angiographic follow up are promising with no recanalisation. Disclosures: M. Piotin: None. A. Biondi: None. N. Sourour: None. C. Mounayer: None. T. Andersson: None. M. Söderman: None. S. Mangiafico: None. M. Jaworski: None. R. Anxionnat: None. R. Blanc: None.